Swelling kinetics of unsaturated polyester–layered silicate nanocomposite: depending on the fabrication method - Katoch, Sunain; Sharma, Vinay; Kundu, Patit Paban (Diffusion Fundamentals, 2010)
Kinetics of swelling and sorption behavior of unsaturated polyester nanocomposite (based on glycolyzed PET, maleic anhydride, styrene, and montmorillonite) synthesized by two different mixing methods, simultaneous and sequential is studied in acetic acid at different temperatures. The values of n in the transport equation are found to be below 0.5, showing non-Fickian or pseudo-Fickian transport in the polymers. The dependence of diffusion coefficient on the mixing methods and temperature has also been studied for the unsaturated polyester nanocomposite. The diffusion coefficients in simultaneous mixing samples decrease with an increase in the mixing time in the samples. In case of the sequential mixing samples, the diffusion coefficient increases with an increase in mixing time. The diffusion coefficient increases with an increase in temperature for all the unsaturated polyester nanocomposite samples. The sorption coefficient increases with an increase in the mixing time for all the samples synthesized by in-situ mixing method. The crosslink density (calculated from the CH3COOH swelling) ranges from 5.014 to 7.092 × 102 mol/cm3 for simultaneous mixed samples and 5.212 to 7.192 × 102 mol/cm3 for sequentially mixed samples.